Microbiological Contamination of Medicinal Products —Is It a Significant Problem? - Stefan Tyski; Magdalena Burza; Agnieszka Ewa Laudy (Pharmaceuticals)
Medicinal products available on the market should be characterised by therapeutic efficacy, high quality, and safety for patients. They must either be sterile or comply with the appropriate pharmacopoeial microbiological purity requirements. Pharmacopoeial monographs related to microbiological tests of drug quality were also referenced. Despite stringent regulations governing pharmaceutical production, irregularities in the microbiological quality of drugs still occur. These are monitored by relevant agencies, which may order the recall of defective product batches from the market. However, in recent years, numerous cases of microbiological contamination in drugs and drug-related infections have been reported. Both isolated incidents and larger outbreaks or epidemics linked to contaminated medicines have been documented. Various microorganisms, including Gram-negative and Gram-positive bacteria, anaerobes, and yeast-like and mould fungi, have been identified in medicinal products or in patients affected by contaminated drugs. Ensuring the appropriate purity or sterility of pharmaceutical raw materials; maintaining cleanliness in the manufacturing environment, facilities, and equipment; and adhering to hygiene protocols and Good Manufacturing Practice regulations are essential for the production of safe and high-quality medicinal products. The aim of this study is to collect and compile information on the microbiological quality of drugs available on the market, with particular attention to identified irregularities, objectionable microorganisms isolated from medicinal products, and drug-related infections.